2018
DOI: 10.1080/21580103.2018.1475307
|View full text |Cite
|
Sign up to set email alerts
|

Elicitor-induced β-glucan contents in fruit body of cauliflower mushroom (Sparassis latifolia)

Abstract: Strain KFRI 723 was used for the cultivation of fruit body to promote the production of b-glucan induced by the elicitor using physical stimulation in the superior cultivated fruit body. Three different elicitor treatments on the physical stimulation (UV, temperature, and harvest time) were treated on the primodia of fruit body. Elicitor controlled by UV light has an effect on the change of the b-glucan contents in flabellae and stipe of cauliflower mushroom, both parts have the highest concentration of b-gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Kim and Kim (1999) previously reported that polysaccharide extracts of G. lucidum have some protective effects against hydroxyl radical-induced DNA strand break. Also, in a study by Ryoo et al (2018), it was reported that a fungus, Sparassis latifolia reacted to UV lamp elicitation by increasing its beta-glucan content, likewise the production of sparassol and methyl orsellinate (Kim et al 2013). This is similar to our findings in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Kim and Kim (1999) previously reported that polysaccharide extracts of G. lucidum have some protective effects against hydroxyl radical-induced DNA strand break. Also, in a study by Ryoo et al (2018), it was reported that a fungus, Sparassis latifolia reacted to UV lamp elicitation by increasing its beta-glucan content, likewise the production of sparassol and methyl orsellinate (Kim et al 2013). This is similar to our findings in this study.…”
Section: Discussionsupporting
confidence: 92%
“…It is being anticipated that UV irradiation can generate stress in fungal cell’s metabolic pathways leading to the synthesis of secondary metabolites in mushrooms, which could be a potential reason for the enhancement in nutraceutical properties of mushroom species (Rathore et al ., 2020; Tiwari et al ., 2021). UV irradiation on mushroom fruit bodies or mycelium produces an elicitation effect to improve their total β‐glucan content (Ryoo et al ., 2018; Rathore et al ., 2020). A recent study (Tiwari et al ., 2021) on powdered Lentinus edodes mushroom has also confirmed that UV irradiation is a vital elicitor agent to enhance β‐glucan content (22.45 to 44.37 g 100 g −1 ).…”
Section: Effect Of Irradiation On Nutraceutical Characteristics Of Mu...mentioning
confidence: 99%
“…Biotic or abiotic elicitors have been employed to enhance the production of β-glucan in S. latifolia. Ryoo et al exploited the effects of physical stimulation of UV irradiation and temperature shock on β-glucan contents in S. latifolia and found that β-glucan yields reached 41.36 ± 2.96% of flabella and 42.16 ± 2.90% of stipe after UV irradiation for 10 min [22]. Park et al utilized chitinase, β-glucuronidase, and lysing enzyme complex as elicitors to enhance the β-glucan content of S. latifolia and produced an increase in β-glucan concentration of 31%, although the treatment caused a decrease in mushroom yield [23].…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the production of desirable compounds in plants or microorganisms, elicitation has been employed using biotic or abiotic elicitors to stimulate the accumulation of secondary metabolites [20,21]. For example, physical elicitation and enzyme treatments have been exploited for the growth enhancement and promotion of β-glucan contents in S. latifolia [22,23]. Alginate is a biotic elicitor that has been demonstrated to provide induced plant defense against pathogens, tolerance improvement to environmental stresses such as drought and salinity, and growth enhancement in Eucomis autumnalis, Vitis vinifera, Phoenix dactylifera, and Olea europaea [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%